2004
DOI: 10.1177/147509020421800403
|View full text |Cite
|
Sign up to set email alerts
|

Integrity of hybrid steel-to-composite joints for marine application

Abstract: There are many instances where the use of weight-saving polymer composite material for an entire structure is either too complex, too expensive or unfeasible. In these circumstances the use of a hybrid structure can incorporate the benefits of traditional (e.g. steel ) construction coupled with the advantages of composite materials [e.g. glass-reinforced polymers, glass-reinforced plastic (GRP)] in weight-critical areas. A number of studies have been carried out on the static strength of hybrid steel-to-compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…The onset of failure was accompanied by a more rapid reduction of stiffness and increase in dissipated energy. These observations agree very well with the findings of Boyd in his study on the integrity of hybrid steel-to-composite joints for marine applications [30].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The onset of failure was accompanied by a more rapid reduction of stiffness and increase in dissipated energy. These observations agree very well with the findings of Boyd in his study on the integrity of hybrid steel-to-composite joints for marine applications [30].…”
Section: Resultssupporting
confidence: 92%
“…After every series of 99 fatigue cycles (at 2Hz), a single slow cycle (0.1Hz) was included because the rate of image capturing by the DIC cameras is limited to 1 picture per second. This allows to determine 10 DIC-based elongation measurements during one slow cycle; a similar methodology is reported in [30]. Load versus elongation data were collected during the slow cycle in order to construct one hysteresis ellipse; a typical plot with experimental data and the fitted loadelongation loop is shown in Fig.…”
Section: Fatigue Testing Methodologymentioning
confidence: 99%
“…Some aspects, such as the static compressive strength and fatigue life characterisation of the connection, were investigated through the European project EUCLID RTP3.21 and the results published in Ref. [4]. Further aspects, such as the consideration of the performance of the joint after artificial hygrothermal ageing, the numerical modelling and prediction of failure of the connection, and the optimisation of the connection for the applied loads is provided in Ref.…”
Section: Shenoi / Composite Materials / 3 Load Transfer Mechanismsmentioning
confidence: 99%
“…Life cycle assessment of composite structures, leading to cradle to grave design concepts, that are better able to account for environmental impact based on energy considerations. 4. Development of concurrent engineering approaches that account for design-production interaction leading to specification of optimal design choices from a costings viewpoint.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that placement of the steel has a significant effect on the strength and should be moved away from the point of stress concentrations. Boyd et al [2004aBoyd et al [ , 2004b describe an embedded metal joint connecting a composite sandwich panel to a steel deck for a helicopter hangar. In this application, a steel plate was embedded at the end of a tapered composite sandwich section panel made from FRP skins and a balsa core.…”
Section: Connections In Hybrid Structuresmentioning
confidence: 99%